Role of sovereign debt on foreign direct investment and economic growth in selected European countries - Tan, Ai Lian (2017)
In the economics literature, investments are reckoned to be a prevalent and powerful instrument to facilitate the growth process. In Europe, FDI has been a crucial part of policy for enhancing productivity and strengthening the association between Europe and the rest of world economy. Nevertheless, the onset of the global financial crisis has triggered an enormous soared of sovereign debt in Europe and threatened the viability of the countries. Against this background, the sharp rise of sovereign debt in European countries has agitated the concern of this study regarding its debt condition on foreign capital and economic growth. First, by applying PMG estimate in 10-selected European countries that covered from 1990-2013, the results reveal a negative sign of sovereign debt on FDI. Hence, this suggests that sovereign debt discourages the inflows of foreign investment in European countries. Second, the results show that FDI becomes insignificant while the interaction term between sovereign debt and FDI is highly significant. Hence, this indicates that the effects of FDI on growth is affected by the sovereign debt condition in European countries. Third, the results of PMG estimate suggest an inverted-U shape of sovereign debt and the threshold value is found to be 76%. Besides, the positive impact of FDI on growth will only kick in when the sovereign debt is below than the threshold value. Based on the findings, several implications of the study can be drawn. Since FDI is important to sustain economic growth, incentives such as a stable macroeconomic condition and company tax policy, better institutional quality and investor protection, transparency, lower bureaucracy and corruption, and necessary reforms of the labor market are important to attract foreign investment to sustain economic growth. Besides, since sovereign debt condition adversely affects FDI flows and FDI-growth nexus, then it is important for the country to provide a stable macroeconomic condition through proper debt management to attract FDI and enhance the ability of the host country to benefit from foreign investment.